2016
DOI: 10.47125/jesam/2016_1/05
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Adaptation Strategies of Smallholder Agroforestry Farmers in the Philippines

Abstract: This article argues that smallholder agroforestry farmers in the selected provinces in the Philippines have already been experiencing climate change in their respective areas as indicated by the change in the rainfall and temperature patterns. Using direct interviews and focus group discussions, the respondent-farmers highlighted that increased incidence of pests and diseases, stunted growth of crops, low crop productivity, delayed planting, delayed fruiting of some crops particularly perenn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 0 publications
3
14
0
Order By: Relevance
“…Results of this study are validated by other similar studies that were conducted in tropical and developing countries (Mutekwa 2009;Landicho et al 2010;Kalinda 2011). Visco et al (2011 highlighted that the smallholder farmers in the Philippines have been experiencing climate change as evidenced by the changing rainfall and temperature patterns over the years.…”
Section: Evidences and Effects Of Climate Change On Agricultural Prod...supporting
confidence: 84%
“…Results of this study are validated by other similar studies that were conducted in tropical and developing countries (Mutekwa 2009;Landicho et al 2010;Kalinda 2011). Visco et al (2011 highlighted that the smallholder farmers in the Philippines have been experiencing climate change as evidenced by the changing rainfall and temperature patterns over the years.…”
Section: Evidences and Effects Of Climate Change On Agricultural Prod...supporting
confidence: 84%
“…Using the literatureā€™s identification of qualitatively and quantitatively compounding events, the highest number of compounding hazards in the adaptation literature is associated with changes in rainfall. Notable climate hazards that compound with drought include extreme heat across the USA, Philippines, Nepal, Zimbabwe, and South Africa 71 , 72 , 73 , 74 , 75 ; mean precipitation decrease in Sierra Leone, Ghana, and Bangladesh; 76 , 77 , 78 pluvial flooding across Nepal, Uganda, Lao, and Vietnam; 79 , 80 , 81 , 82 and wildfire in the USA. 83 While 20 (38%) articles did describe the responses to spatially or temporally compound impacts or events, 33 (62%) articles did not refer explicitly to compound climate events and therefore did not fully acknowledge the compound nature of the climate events associated with the observed impacts.…”
Section: Resultsmentioning
confidence: 99%
“… 99 Temporally compounding vulnerabilities are described in the interactions over time among food insecurity, immobility, chronic health challenges, and migrant status for communities affected by extreme heat in Bukavu in DR Congo 115 and heat and drought in the Philippines. 74 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Building from previous capacity building projects (Landicho et al, 2009), the project collaborators believed that farmers learn https://doi.org/10.30852/sb.2022.1757 form of spatial arrangements or temporal sequence on the same land to diversify and sustain production for increased social, economic and environmental benefits (Leakey, Temu, Melnyk, & Vantomme, 1996). A number of studies have shown that agroforestry offers potential in enhancing the socio-economic productivity of the farmers because of the diverse crop components (Landicho et al, 2016;Tolentino, Landicho, De Luna, & Cabahug, 2010;Cunningham, Nicholson, Yaou, & Rinaudo, 2008) while at the same time addresses the ecological dimension (Baliton et al, 2020;Palma & Carandang, 2014;Casas, Marin, Toledo-Bruno, Lacandula, & Aguinsatan, 2014).…”
Section: Resultsmentioning
confidence: 99%